Polyurethane-grafted chitosan as new biomaterials for controlled drug delivery - Mahanta A.K.; Mittal V.; Singh N.; Dash D.; Malik S.; Kumar M.; Maiti P. (My University, 2025)
The present investigation focuses on the grafting of chitosan (CHT) with diisocyanate terminated polyurethane. Solid state 13C NMR spectroscopy confirms the grafting reaction and the degree of substitution (DS) was calculated from the deconvoluted area of the corresponding NMR peak. Solubility studies, swelling behavior and contact angle measurements support the hydrophobic chemical modification on CHT molecules and higher DS leads to the cross-linking of CHT molecules having polyurethane bridges resulting insolubility and regulated swelling in the graft copolymer. Molecular relaxations phenomena due to the constraint associated with the grafting have been revealed using spin-lattice relaxation tine (T1) and shifting of peak position in tan δ curve toward lower temperature in dynamic mechanical measurement at constant frequency indicating flexible nature of graft copolymers as compared to pure CHT. The sustained drug delivery has been achieved using graft copolymers vis-à-vis pure CHT following the Fickian diffusion behavior (n ≤ 0.45) and the release rate can be tuned by altering the DS. In depth biocompatibility studies through platelet aggregation, platelet adhesion, reactive oxygen species of the developed graft copolymers, and in vitro hemolysis assay and cell viability have been performed to understand its potential use in biomedical applications and compared the improved properties with respect to pure CHT. Hence, bio- and hemocompatible CHT graft copolymers have been developed with the capability of controlled and sustained drug release. © 2015 American Chemical Society.